Small-Signal Modeling of mm- Wave MOSFET up to 110 GHz in 22nm FDSOI Technology - Quang Huy Le; Dang Khoa Huynh; Defu Wang; Thomas Kämpfe; Matthias Rudolph (2019 IEEE Asia-Pacific Microwave Conference (APMC), 2019)
In this paper, a comprehensive analysis on small-signal modeling of mm-wave transistor in 22nm FDSOI technology is presented. The model is constructed based on experimental S-parameters up to 110 GHz of a 22FDX® thick-oxide n-MOSFET and analytical parameter extraction approach. The non-quasi static effect is addressed thoroughly in the equivalent circuit model for high frequency validity. The bias-dependent series source and drain resistances are considered to account for the overlap regions between the gate and the highly doped source/drain regions. In addition, a simple RC network is included at the output to model the innegligible substrate coupling at mm-wave frequencies. Excellent agreements between model prediction and measurement are observed in the interested bandwidth for various bias conditions.